2001
DOI: 10.1046/j.1440-6055.2001.00202.x
|View full text |Cite
|
Sign up to set email alerts
|

Distribution and ecology of the lucerne flea, Sminthurus viridis (L.) (Collembola: Sminthuridae), in irrigated lucerne in the Hunter dairying region of New South Wales

Abstract: The lucerne flea, Sminthurus viridis (L.), is shown to be a pest of irrigated lucerne in the summerrainfall, temperate-type climate of the Hunter region in New South Wales, an area previously considered unsuitable for its establishment. Main activity occurred at average temperatures ≤ 13-15°C, resulting in five generations per season. Establishment and activity were closely related to irrigation. Eggs hatched throughout summer but populations failed to develop. It was unclear if diapausing eggs, the progressiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
24
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(25 citation statements)
references
References 14 publications
1
24
0
Order By: Relevance
“…The data presented here is consistent with previous studies (Davidson 1934, Wallace 1967, Bishop et al 2001a) with at least two generations of S. viridis occurring per season. Typically, an autumnÐwinter generation hatches from diapause eggs and another generation in spring lays diapause eggs.…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…The data presented here is consistent with previous studies (Davidson 1934, Wallace 1967, Bishop et al 2001a) with at least two generations of S. viridis occurring per season. Typically, an autumnÐwinter generation hatches from diapause eggs and another generation in spring lays diapause eggs.…”
Section: Discussionsupporting
confidence: 92%
“…Previous studies have consistently found two peak abundance periods that result from autumn emergence of the Þrst generation and then from favorable spring conditions (Davidson 1934, Wallace 1967, Bishop et al 2001a). However, considerable variation has been observed for the number of generations that occur, with between three and Þve relatively distinct generations reported (Davidson 1934, Wallace 1967, Bishop et al 2001a).…”
mentioning
confidence: 87%
See 3 more Smart Citations